Improved perinatal health through qualified antenatal care in urban Phnom Penh, Cambodia - Ngy, Mean-Heng (Springer-Verlag, 2007)
OBJECTIVES: The aim of this study is to examine the utilities of antenatal care with comprehensive health education qualified in Phnom Penh for the health of mothers and infants during perinatal and postpartum periods. Attention was given to the existing socioeconomic disparties among women in this urban area, and the utilities were discussed irrespective of socioeconomic status. METHODS: A total of 436 pregnant women in an urban area in Phnom Penh were selected using a complete survey in randomly sampled villages and were followed up. Participating in antenatal care with comprehensive health education at least three time was regarded as the use of “qualified antenatal care” during pregnancy. In this study, we investigated the independent associations of the use of qualified antenatal care with the following outcome variables after the adjustment for the influence of socieconomic variables: postpartum maternal health knowledge, postpartum maternal anemia, low birth weight, and infant immunization. RESULTS: Of the 314 subjects who completed the follow-up examination, 66.8% used qualified antenatal care during pregnancy. The use of qualified antenatal care was positively associated with postpartum maternal health knowledge (OR=2.38, 95% CI: 1.12–5.05). and reductions in the incidences of postpartum anemia (OR=0.22,95% CI: 0.05–0.95) and low birth weight (OR=0.05,95% CI: 0.01–0.39) after the adjustment of the influence of socioeconomic status. The infants born to mothers who used qualified antenatal care had significantly higher coverage of BCG, DPT(1), and DTP(3) immunizations (P<0.001,P<0.001, andP<0.01, respectively), independent of their socioeconomic conditions. CONCLUSION: This study shows the solid utilities of qualified antenatal care in Phnom Penh for perinatal health.